2014
DOI: 10.1039/c4cc04009k
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxometalate-functionalized metal–organic frameworks with improved water retention and uniform proton-conducting pathways in three orthogonal directions

Abstract: Polyoxometalate-functionalized metal-organic frameworks featuring uniform proton-conducting pathways in three orthogonal directions, good water retention and stability were prepared. The proton conductivity of the hybrid material was observed to increase by 5 orders of magnitude compared to that of the parent material HKUST-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
64
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 49 publications
6
64
1
Order By: Relevance
“…Meanwhile, since Fe 3 O 4 @NENU‐3 is similar to Fe 3 O 4 @HKUST‐1 based on the synthesis condition except that the former contains the embedded HPW, it is expected that their diffraction patterns are also similar to each other. Based on the result, the PXRD pattern of Fe 3 O 4 @NENU‐3 demonstrated similar diffraction peaks with the synthesized Fe 3 O 4 @HKUST‐1 composite as well as the pristine NENU‐3, as shown in Figure A.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Meanwhile, since Fe 3 O 4 @NENU‐3 is similar to Fe 3 O 4 @HKUST‐1 based on the synthesis condition except that the former contains the embedded HPW, it is expected that their diffraction patterns are also similar to each other. Based on the result, the PXRD pattern of Fe 3 O 4 @NENU‐3 demonstrated similar diffraction peaks with the synthesized Fe 3 O 4 @HKUST‐1 composite as well as the pristine NENU‐3, as shown in Figure A.…”
Section: Resultssupporting
confidence: 86%
“…Fe 3 O 4 @HKUST‐1 and Fe 3 O 4 @NENU‐3 exhibited contact angles in deionized water of 43° and 24°, respectively. The good hydrophilicity of Fe 3 O 4 @NENU‐3 is due to the embedded HPW within the MOFs framework, which is similar to the previous report . Furthermore, the water stabilities of MFCs were determined by monitoring their structural characteristics based on optical observation and PXRD measurement.…”
Section: Resultsmentioning
confidence: 99%
“…Whereafter, we introduce the Schiff base ligand N,N 0 -bis(furan-2-ylmethylene)hydrazin L to obtain a 2D Wells-Dawson-based coordination polymer H 0.5 Ag 0. 5 [16]. These results can provide an experimental basis for further studies on the construction of metal-Schiff base species and POM-based compounds.…”
Section: Introductionmentioning
confidence: 83%
“…Currently, the design and synthesis of POM-based inorganic-organic hybrid materials is not only an emerging multidisciplinary research area but also one of the biggest areas in POM chemistry. One of the effective strategies in the construction of POM-based composites is to functionalize POMs with transition-metal compounds (TMCs) [4,5]. Because of the large number of potential coordination sites of POMs, incorporating them into metal-organic species may facilitate the production of new architectures with fascinating structures and modified properties [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] An aspect of the research in materials science has reported about the electrochemical performances about these compounds. [1][2][3][4][5][6][7] An aspect of the research in materials science has reported about the electrochemical performances about these compounds.…”
mentioning
confidence: 99%